Implementasi nilai-nilai filosofis budaya Jawa sebagai pedoman pendidikan karakter di era milenial - Iin, Khofifa Khurin (Maliki Interdisciplinary Journal, 2023)
Every nation in this world has values or principles that serve as a philosophical basis in providing direction for life. Noble values that are upheld are based on religious teachings and rules of life that are belived to be true by the community. However, these noble values began to erode because they were eroded by the times and globalization. In the current era of development, generations appear with two antagonistic faces. On the one hand, it succeeded in achieving rapid development in the field of science and technology, on the other hand, it also brougght setbacks in the form of milennial generation who experienced spiritual tribulations, in the form of a decline in morals, one’s character and other problems. The basic problem related to the problem above is the realization of education that only emphazises knowledge without regard to one’s character education, so the author chooses to explore the philosophical values of javanese culture which have very beautiful meanings and are relevant to be implemented in one’s character education, especially the current millenial generation.